Investigating Energy-Saving Strategies: A Numerical Study of Translucent Insulation and Phase Change Materials in Windows - Ubaid ur Rehman; Muhammad Ashiq; Muhammad Ahmad Rafi; Usama Malik; Waqas Javid; Mehmood ul Hassan Amjad (Engineering Proceedings, 2023)
In Pakistan, residential energy consumption is predominantly devoted to ensuring thermal comfort, making energy reduction a significant task in building load management. Windows, which are notorious for having poor thermal barriers, contribute considerably to energy losses under harsh weather conditions. Incorporating high thermal inertia materials in windows, such as transparent insulation materials (TIM) and phase change materials (PCM), offers the potential for energy reduction. Using numerical simulations in ANSYS Fluent, this study compares three window types and explores their influence on interior temperature. The findings show that PCM-based windows have a low temperature increase during the melting phase, indicating their great energy-saving potential. Furthermore, PCM absorbs almost 90% of exposed heat, emphasizing its usefulness for energy saving in the Pakistani building industry.